Quantitative and qualitative changes in human Meissner’s corpuscle at different ages: a light microscopic analysis - Bhat, Gh Mohd; Itoo, Mohd Saleem; Shah, Bashir Ahmad; Shah, Naseer Ahmad; Banno, Shameema; Hussain, Tajamul (International Journal of Research in Medical Sciences, 2017)
Background:Meissner’s corpuscle is the most complex sensory receptors of the skin; providing information about rapidly fluctuating mechanical forces acting on the hairless skin. Aim of current study was to study density and structural changes in human Meissner’s corpuscles at different ages Methods:Samples were obtained from finger tips of fifteen persons and divided into three groups according to age: group A <15years; group B: 16-45 years and group C: 46-72 years. 5 µm thick sections were prepared, impregnated with silver and observed under compound light microscope. Density of Meissner’s corpuscles (Mcs) was studied by calculating Meissner’s Index (MI). Results:In group A, the MI was 0.86-0.90, which increased to 0.96 in group B and dropped in group C to 0.4 (in the seventh decade). The analysis of variance showed significant difference (P = 0.019) in MIs of the three age groups. The size of the Mcs was largest in group B, followed by group C and smallest in group A. The analysis of variance showed that there was highly significant difference (P = 0.003) between the size of Mcs in all the three age groups. It was observed that morphology of Mcs alter with age. In children these consisted of rudimentary coil of nerve fibers around collection of cells. In adults the intra-corpuscular nerve fibers were compressed into a tight spiral and modifications of nerve fibers, like end bulbs, varicosities and networks, were well developed. In old age Mcs were attenuated consisting of tangled mass of nerve fibers. Conclusion:It can be concluded that in adults the Mcs are greater in number, larger in size and complicated in structure, compared to young and old people.